Molecular profile of non-small cell lung cancer in northeastern Brazil - Oliveira,Ana Claudia da Silva Mendes de (2019)
ABSTRACT Objective: To investigate the histological subtypes and mutational profiles of non-small cell lung cancer in Brazil, looking for correlations among histological subtypes, expression of anaplastic lymphoma kinase (ALK), EGFR mutation status, and programmed death-ligand 1 (PD-L1) expression. Methods: We evaluated 173 specimens obtained from patients with lung adenocarcinoma in northeastern Brazil. Expression of PD-L1 and ALK was evaluated by immunohistochemistry; EGFR mutation status was evaluated by sequencing. We categorized the histological subtypes in accordance with the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society classification. Results: The most common histological subtypes of lung adenocarcinoma were solid predominant (in 46.8%), acinar predominant (in 37.0%), and lepidic predominant (in 9.8%). ALK expression was detected in 10.4% of the samples, and 22.0% of the tumors harbored EGFR mutations. The most common EGFR mutation was an exon 21 L858R point mutation (in 45.5%), followed by an exon 19 deletion (in 36.3%). The tumor proportion score for PD-L1 expression was ≥ 50% in 18.2% of the samples, 1-49% in 32.7%, and 0% in 49.5%. The solid predominant subtype was significantly associated with wild-type EGFR status (p = 0.047). Positivity for PD-L1 expression was not found to be significantly associated with ALK expression or EGFR mutation status. Conclusions: Our results suggest that the molecular profile of non-small cell lung cancer in northeastern Brazil differs from those of populations in other regions of the country, with ALK positivity being higher than the other biomarkers. Further studies including clinical and genetic information are required to confirm these differences, as well as studies focusing on populations living in different areas of the country.